The Path of Pancasila Ideology: Legislation and Philosophical Approach in Policy Arrangement for National Ideology - Efendi, Bahtiyar; Cahyono, Ma’ruf (APPTHI, 2020)
The success of the state in realizing its goals is not only because the state has an ideology but is also determined by the good values ​​that exist in the quality of humans or individuals in a nation. It means that to make it happen, a good and equal understanding of the values ​​contained in the ideology requires concrete policies, which are actualized in the attitude of social life. In other words, ideology must become a real character of a nation. The implementation of the Pancasila Ideology Development has not been carried out optimally because the regulatory framework that regulates the Pancasila Ideology development is still scattered in various regulations. This issue is important to be studied more deeply considering the direction of the regulation of Pancasila Ideology development has a very important meaning, especially related to policies in the regulation field, which will greatly influence the success of Pancasila ideology development to strengthen national resilience. This study uses qualitative methods through document analysis. The data was analyzed related to documents related to the development of the Pancasila ideology. The draft implementing regulations that are needed to describe the level of implementation of the basic Pancasila ideology development is the need for implementing regulations that regulate procedures for the implementation of pancasila ideology development and roadmap for pancasila ideology development and procedures for monitoring and evaluation of the implementation of pancasila ideology development. With the principles of fostering the Pancasila ideology outlined in a law-level regulation, it is hoped that this regulation can become a policy direction with a stronger legal basis in the context of fostering the Pancasila ideology, which is national and binding on all state administrators and elements of society. Abstrak Keberhasilan negara dalam mewujudkan tujuannya bukan hanya karena negara memiliki ideologi, tetapi juga ditentukan oleh nilai-nilai baik yang ada pada kualitas manusia atau individu dalam suatu bangsa. Artinya untuk mewujudkannya, pemahaman yang baik dan setara terhadap nilai-nilai yang terkandung dalam ideologi memerlukan kebijakan-kebijakan yang konkrit, yang diaktualisasikan dalam sikap kehidupan bermasyarakat, dengan kata lain ideologi harus menjadi karakter nyata suatu bangsa. Pelaksanaan Pembinaan Ideologi Pancasila belum terlaksana secara maksimal karena kerangka regulasi yang mengatur tentang Pembinaan Ideologi Pancasila masih tersebar di berbagai regulasi. Masalah ini penting untuk dikaji lebih dalam mengingat arah pengaturan pengembangan Ideologi Pancasila memiliki arti yang sangat penting, terutama terkait kebijakan di bidang regulasi yang akan sangat mempengaruhi keberhasilan pengembangan ideologi Pancasila dalam rangka memperkuat ketahanan nasional. Dalam penelitian ini, menggunakan metode kualitatif, melalui analisis dokumen. Dalam menggunakan metode kualitatif, data penelitian akan dianalisis terkait dengan dokumen-dokumen yang terkait dengan perkembangan ideologi Pancasila. Rancangan peraturan pelaksanaan yang diperlukan untuk menggambarkan tingkat pelaksanaan pembangunan ideologi Pancasila yang bersifat mendasar adalah perlunya peraturan pelaksanaan yang mengatur. tata cara pelaksanaan pengembangan ideologi pancasila dan roadmap pengembangan ideologi Pancasila dan tata cara monitoring dan evaluasi pelaksanaan pengembangan ideologi Pancasila. Dengan prinsip-prinsip pembinaan ideologi Pancasila yang dituangkan dalam suatu peraturan perundang-undangan, diharapkan peraturan ini dapat menjadi arah kebijakan yang memiliki landasan hukum yang lebih kuat dalam rangka pembinaan ideologi Pancasila yang bersifat nasional dan mengikat seluruh negara. pengurus dan unsur masyarakat. Kata kunci: Pancasila, Legislasi, Pembangunan Ideologi Nasional, Indonesia